Drained Bearing Capacity of Strip Footings on Two-Layered Sand Soil Slope - Benali, Redha; Mazouz, Badis; Belkadi, Ahmed Abderraouf; Mansouri, Tarek; Goudjil, Kamel (Engineering, Technology & Applied Science Research, 2024)
The objective of this study is to investigate the drained bearing capacity of a strip footing on a two-layered sand slope through the use of numerical analysis. The analysis is conducted using Plaxis, a two-dimensional finite element software. The behavior of the sand is modeled utilizing the non-linear Mohr-Coulomb criteria. The research examines the influence of various parameters on the footing’s behavior, including the normalized thickness of the top layer h1/B, slope angle β, and friction angles of both loose and dense sand, φ1 and φ2, respectively. The findings indicate that for the scenarios with a denser top layer φ1/φ2 > 1, the bearing capacity increases with rising h1/B. Conversely, for the cases with a looser top layer φ1/φ2 < 1, the bearing capacity declines with increasing h1/B. Moreover, irrespective of the slope angle β, the bearing capacity rises with a higher sand friction angle φ.